2011
DOI: 10.1002/qj.814
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism for ocean–atmosphere coupling in midlatitudes

Abstract: The role of moist convection in 'transferring' upward surface ocean conditions throughout the troposphere is studied using reanalysis data for the extratropical Northern and Southern Hemispheres in winter. It is found that conditions for the development of a convective air column from the sea surface to the tropopause are met frequently over all major western boundary currents and their extension in the oceanic interior (sometimes for as much as 50% of the time). These frequent occurrences are shown to be join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…6e), in which the baroclinic vertical structure of the u response is evident. The significant positive u anomaly of 0.2-0.3 K extends up to 300 hPa and is accompanied by the ascending motion (Czaja and Blunt 2011;Smirnov et al 2015;Wills et al 2016), while the significant negative u anomaly of 0.2-0.3 K up to 600 hPa is coincident with the descending motion. The deeper extension of the diabatic heating than the cooling is consistent with the finding by Révelard et al (2016), who attributed the uneven vertical distribution of the heating and cooling to the primary cause of the nonlinearity in observed circulation response to the changes in the Kuroshio Extension front (Qiu et al 2014).…”
Section: Vertical Distribution Of the Responsementioning
confidence: 93%
“…6e), in which the baroclinic vertical structure of the u response is evident. The significant positive u anomaly of 0.2-0.3 K extends up to 300 hPa and is accompanied by the ascending motion (Czaja and Blunt 2011;Smirnov et al 2015;Wills et al 2016), while the significant negative u anomaly of 0.2-0.3 K up to 600 hPa is coincident with the descending motion. The deeper extension of the diabatic heating than the cooling is consistent with the finding by Révelard et al (2016), who attributed the uneven vertical distribution of the heating and cooling to the primary cause of the nonlinearity in observed circulation response to the changes in the Kuroshio Extension front (Qiu et al 2014).…”
Section: Vertical Distribution Of the Responsementioning
confidence: 93%
“…In the upper troposphere the circulation forms two cells with northward (southward) flow north (south) of the front in HR, whereas the flow is southward at all latitudes in LR. The larger low-level u E anomaly in HR over the warm SST, reflecting both warmer temperatures and enhanced low-level moisture, also reduces the low-level stability (not shown), in a region that is frequently convectively unstable (Czaja and Blunt 2011;Sheldon and Czaja 2014). The zonal wind response is weak in both simulations (not shown): in the LR, zonal wind changes are less than about 1.5 m s 21 and are consistent with the cyclonic circulation to the east, while the HR zonal wind changes are of opposite sign and even smaller.…”
Section: Atmospheric Response To An Oyashio Extension Frontal Shiftmentioning
confidence: 96%
“…Moreover, the region of storm track and strong transient eddy activities is corresponding to the oceanic front zone in the midlatitudes. In recent years, observational studies with high-resolution satellite data (Nakamura et al 2004;Small et al 2008) and numerical studies with high-resolution GCM Taguchi et al 2009;Sampe et al 2010;Czaja and Blunt 2011;Feliks et al 2004Feliks et al , 2007Feliks et al , 2011 have shown that the SST anomalies associated with midlatitude oceanic front zones can influence the time-mean atmospheric circulation beyond planetary boundary layer. Therefore, the transient eddies not only play an important role in driving and maintaining midlatitude atmospheric circulation (Ren et al 2011;Xiang and Yang 2012;Zhang et al 2012;Nie et al 2013Nie et al , 2014, but also may act as a main dynamical process through which the midlatitude ocean thermal condition can affect the atmosphere (Ren et al 2007).…”
Section: Introductionmentioning
confidence: 99%